Exploring Feminine Identity in Nano Riantiarno’s Opera Primadona: A Feminist Literary Analysis - Yolla Fitria; Iswadi Bahardur; Samsiarni (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2024)
This research is motivated by the depiction of the image of female characters depicted by male authors. This study aims to describe the image of women in the Opera Primadona drama script. The method used is a qualitative descriptive method. The data source used in the study is the Opera Primadona drama script book. In this study, the researcher used investigator triangulation to check the data. The data collection technique is by using the reading-note technique. Data reduction, analysis, and conclusion are used to analyse data. The study results show that First , women's self-image includes physical and psychological aspects depicted in the Opera Primadona drama script by Nano Riantiarno. The physical characteristics depicted are about the characters Kejora and Kecubung, who are adult women. In contrast, the characteristics of the psychological aspect are female characters who have responsibilities to themselves and others. Second, the social image of women can be seen from the social image in the family and society. The social image in the family is that the characters Kejora and Kecubung try to be good wives and mothers even though they face several problems. While the social image in society is depicted, Kejora and Amethyst became part of the opera in performances among the people.